Medical decision-support systems and the concept of context. - Karlsson, D. (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
Medical decision-support systems are of necessity multi-contextual in nature. There are always at least two contexts involved in the use of such systems: the expert knowledge-provider context and the end-user context. To show this, we present examples of context-dependent aspects significant to the use of decision-support systems. The existence of discrepancies between the contexts threatens to disrupt the rationale for using decision-support systems: for the system to transfer knowledge from the expert to the end-user. Both theoretical and empirical studies show that such discrepancies exist and that they may be detrimental to the use of decision-support systems. Systems must thus give support in interpreting the output produced by the system in the context of the end-user.